Hari-hari terpanjang menjelang mundurnya Presiden Soeharto dan beberapa peristiwa terkait - Luhulima, James (Jakarta : Penerbit Kompas, 2001)
Political conditions during the time of Soeharto's stepdown, the 2nd president of Indonesia, in 1998.
'Mei 2001.'
Includes bibliographical references (p. 248-250) and index.
Keywords: Soeharto, -- 1921-2008.; Indonesia -- Politics and government -- 1966-1998.